TRANSFORMATION OF ISLAMIC EDUCATION MANAGEMENT ADDRESSING THE CHALLENGES OF THE 21ST CENTURY - Astuti, Siwi; Nasrudin Harahap; Nurul Hidayati Murtafiah (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
In the rapidly evolving landscape of the 21st century, the field of education faces unprecedented challenges that demand innovative solutions. This study delves into the transformation of Islamic education management as a response to the challenges posed by the 21st-century era. Drawing on a blend of qualitative and quantitative research methodologies, this research explores the theoretical underpinnings of educational management, the principles of transformative education, and the specific issues confronting Islamic education in the contemporary era. By analyzing the findings, this study illuminates how the strategic transformation of Islamic education management can effectively address the multifaceted challenges presented by the 21st century. The conclusions drawn from this study emphasize the significance of reimagining traditional educational practices to align with the demands of the modern world, while remaining rooted in the principles of Islamic pedagogy and values.